Pemanfa’atan E-Comerce Tik - Tok Live Sebagai Sarana Dalam Pemasaran Produk pada PT. PLM - Bambang Permadi; Muhammad Ikhsan Harahap (Jurnal Anestesi, 2024)
The use of Uses and Gratifications Theory in the context of TikTok Live is a key strategy in overcoming the challenge of lack of effective product introduction to consumers. This theory reveals that TikTok Live users actively seek satisfaction through media, focusing on detailed product information. This research utilizes this theoretical framework to design more effective product marketing strategies, meeting consumer needs and desires. This research was conducted based on the results of observations or observations that the researcher had carried out for 1 (one) month. This research was conducted at PT. PLM JAYA which is located on Jl. Hajj Hospital No. 67 Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The application of Uses and Gratifications Theory in TikTok Live illustrates that users seek entertainment, social interaction, and fulfill personal needs when watching live broadcasts. They actively select broadcasts that suit their needs, enabling more informed and targeted purchasing decisions. This makes TikTok Live an effective platform in meeting user wants and needs and increasing the effectiveness of product marketing through social interaction and entertainment content. In the age of social media, especially on platforms like TikTok, product marketing has become increasingly creative and focused on entertainment. The entertainment appeal presented to users provides an opportunity for companies to convey their message in unexpected ways and direct user interest towards their products. With an innovative approach, product marketing on TikTok and similar platforms continues to develop into an important part of modern business strategy.